1998
DOI: 10.1046/j.1365-2567.1998.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Different endothelins stimulate cytokine production by peritoneal macrophages and microglial cell line

Abstract: Endothelins (ETs), potent vasoconstricting peptides, are produced by macrophages upon stimulation and may participate in the amplification or regulation of the inflammatory response. However, it is not clear whether ETs can act in an autocrine manner on macrophages and which role they play in relationship with other cytokines. To address these issues, we studied the effects of ETs on the production of inflammatory cytokines by mouse peritoneal macrophages or by a retrovirus-transformed microglial cell line. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
2
20
0
1
Order By: Relevance
“…It also fits well with reports that CRF triggers the release of a preformed hypothalamic pool of IL-1␤ (34) and that IL-1 enhances central sympathetic outflow when given intracerebroventricularly (23) and causes fever when microinjected into the preoptic area (POA) (17). Furthermore, ET-1 stimulates IL-1 release from different cell types, including macrophages, microglia, and astrocytes (6,31). The increase in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…It also fits well with reports that CRF triggers the release of a preformed hypothalamic pool of IL-1␤ (34) and that IL-1 enhances central sympathetic outflow when given intracerebroventricularly (23) and causes fever when microinjected into the preoptic area (POA) (17). Furthermore, ET-1 stimulates IL-1 release from different cell types, including macrophages, microglia, and astrocytes (6,31). The increase in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…ET-1 can in turn modulate the endothelial expression of adhesion molecules and cytokines production (McCarron et al, 1993;Speciale et al, 1998). Local administration of endothelin-1 induces mucosal ulcerations (LopezBelmonte and Whittle, 1994) and endothelin antagonism has been demonstrated to protect against mucosal ulceration induced by HCl and indomethacin.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that ETs can also regulate amoeboid microglia through an autocrine manner in their synthesis and secretion of chemokines, MCP-1 and SDF-1. This view lends it support from the studies showing that ET-1 and ET-3 can stimulate microglial cells in the prodution of IL-1 and IL-6 (Speciale et al, 1998), and that monocyte chemoattractant protein-1 (MCP-1) production in macrophages is regulated by ETs (Chen et al, 2001). The specific localization of ETs in amoeboid microglia in this study has therefore greatly amplified the multiple functional roles of these peptides in the CNS, especially in the development stage.…”
Section: Discussionmentioning
confidence: 60%
“…Speciale et al (1998) had reported that different ETs stimulate cytokines production, such as IL-1 and IL-6 by mouse macrophages. The present RT-PCR study has shown that ET-1 mRNA coupled with that of MCP-1 and SDF-1 is markedly upregulated.…”
Section: Discussionmentioning
confidence: 99%